A systematic review of the qualitative literature on older individuals' experiences of care and well‐being during physical rehabilitation for acquired brain injury. (16th August 2021) - Lafiatoglou, Panagiota; Ellis‐Hill, Caroline; Gouva, Mary; Ploumis, Avraam; Mantzoukas, Stefanos
Abstract: Aims: To acquire an in‐depth understanding of how older individuals diagnosed with acquired brain injury (ABI) experience their well‐being and care when undergoing physical rehabilitation. Design: Systematic literature review. Data sources: The electronic databases of PubMed, CINAHL, APA PsycInfo, ASSIA and SCOPUS were searched from 2005 to 2020. Extensive reference checking was also conducted. Review methods: A systematic review was conducted following PRISMA guidelines, including predominantly qualitative studies. Studies' quality was appraised using the critical apraisal skills programme (CASP) tool. Results: Seventeen studies met the inclusion criteria. Following methods of thematic synthesis, four overarching interpretive themes were identified: (a) Rehabilitation processes and their impact on older individuals' well‐being; (b) Identity and embodiment concerns of older individuals during rehabilitation; (c) Institutional factors affecting older individuals' care and well‐being experiences; and (d) Older individuals' participation in creative activities as part of rehabilitation. Conclusion: Organizational and structural care deficiencies as well as health disparities can adversely impact older individuals' autonomous decision‐making and goal‐setting potentials. The discrepancy between older individuals' expectations and the reality of returning home along with the illusionary wish to return to a perceived normality, can further negatively affect older individuals' sense of well‐being. Constructive communication, emotional support, family involvement in rehabilitation and creating a stimulating, enriching social environment can humanize and facilitate older individuals' adjustment to their new reality following ABI. Impact: There is a lack of qualitative research on older individuals' ABI rehabilitation experiences, especially traumatic brain injury incidents. Further study should consider patients' concerns over their involvement in decision‐making and goal setting about their care. Overall, this review reveals the need to examine further the significance of humanizing care and the factors that affect older individuals' sense of well‐being.